INCREASING BUSINESS ACTIVITY IN THE SPHERE OF TOURISM SERVICES (World Economics and Finance Bulletin, 2022)
This article discusses the issues of expanding and further accelerating entrepreneurial activity in the field of tourism. Proposed measures for the development and support of entrepreneurial activity in the field of tourism.
Keywords: tourism; entrepreneurship; entrepreneurial activity; innovation